Further considerations of theory, technique, and affect in child psychoanalysis: Two prelatency cases. (15th June 2015) - Holinger, Paul C.
Translations of summary: The analyses of two young boys, 4½ and 5 years old, are presented. One child was severely inhibited and nearly mute; the other was disorganized, frenetic, and violent. In the context of these treatments, the author raises several questions related to clinical theory and technique, including the use of early interpretation of affect with such children; the possible benefit of verbalizing primary affects in this early interpretive work; and the roles of verbalization and affect in work with caregivers and adult patients.